What are Edthechs? A systematic literature review - Silva e Meirelles, Dimária; Miguel Lopes, Yan (Revista Eletrônica de Administração, 2024)
In contrast to the recurring drop of demand in traditional education institutions, it is noticed a rapid expansion of Edtechs. Considered as educational startups with alternative learning models and innovative methodologies based on multidisciplinary collaboration, we do not know much from a theoretical point of view about their specific characteristics, which contrasts with traditional teaching modalities. This article aims to evaluate the literature about Edtechs, assessing both the adopted concept and the challenges and trends regarding the future of these new educational institutions. The methodology used was a literature review divided into two stages. The first stage was quantitative, focusing on the volume of publications by author, journal, and other descriptive information. The second stage was qualitative, focusing on the content of the published articles. The quantitative analysis allowed us to conclude that studies on the topic are recent and have a growing publication trend, but there is no publication concentration in journals. The qualitative analysis concluded that Edtechs have a social mission to mobilize new technologies to transform and improve the reach and quality of education and student’s life and career prospects. This research is relevant for the academic and corporate community interested in the topic, as it consolidates all the scientific knowledge about Edtechs.